THE REDUCTION ANTHROPOGENIC EMISSION AT THE COMBUSTION OF COALS AND COAL PROCESSING WASTE AS A COMPONENT COAL-WATER SLURRY CONTAINING PETROCHEMICALS - M. A. Dmitrienko; G. S. Nyashina; N. E. Shlegel; S. A. Shevyrev (Известия высших учебных заведений: Проблемы энергетики)
Coal-fired power stations produce of tens millions tons of ash and slag waste, and hundreds of millions cubic meters of gas emissions annual. As part of this work analysis of current methods to reduce anthropogenic emissions in the ash produced by the processing (combustion) of traditional coal fuels was made, advantages and disadvantages of each methods were highlighted. It is shown that both low levels of emissions in the ash and combustion products is difficult to ensure. As a result, it was proposed to use promising coal-water slurry containing petrochemicals instead of pulverized coal. The experimental research into maximum concentrations of anthropogenic emissions from the combustions of coal-water slurry containing petrochemicals. The experimental research into maximum concentrations of anthropogenic emissions by the combustions of coal-water slurry containing petrochemicals basedfilter-cakes were conducted